2018
DOI: 10.1002/jcp.27644
|View full text |Cite
|
Sign up to set email alerts
|

Generation of functional human pancreatic organoids by transplants of embryonic stem cell derivatives in a 3D‐printed tissue trapper

Abstract: Organoids can be regarded as a beneficial tool for discovery of new therapeutics for diabetes and/or maturation of pancreatic progenitors (PP) towards β cells. Here, we devised a strategy to enhance maturation of PP by assembly of three‐dimensional (3D) pancreatic organoids (PO) containing human embryonic stem (ES) cell derivatives including ES‐derived pancreatic duodenal homeobox 1 (PDX1) + early PP, mesenchymal stem cells, and endothelial cells at an optimized cell ratio, on Matrigel. The PO was placed in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…Interestingly, both hPOs generated fetal pancreatic‐like structures suggesting that the perinatal CF phenotype was not a result of altered pancreatic development (Hohwieler et al ., 2017). In another study, organoids were engineered via co‐culture of three separate cell types (Soltanian et al ., 2018). Both hPSC‐derived endothelial cells and hPSC‐derived MSCs were established and co‐cultured with hPSC‐derived pancreatic progenitors on growth factor‐reduced MG to generate hPOs.…”
Section: Imaging Organoids and In Vivo Transplantationmentioning
confidence: 99%
“…Interestingly, both hPOs generated fetal pancreatic‐like structures suggesting that the perinatal CF phenotype was not a result of altered pancreatic development (Hohwieler et al ., 2017). In another study, organoids were engineered via co‐culture of three separate cell types (Soltanian et al ., 2018). Both hPSC‐derived endothelial cells and hPSC‐derived MSCs were established and co‐cultured with hPSC‐derived pancreatic progenitors on growth factor‐reduced MG to generate hPOs.…”
Section: Imaging Organoids and In Vivo Transplantationmentioning
confidence: 99%
“…31,53,93,102,106,195197 Furthermore, it was shown that successful differentiation into early ISC is possible in vitro; maturation, however, requires in vivo conditions. 31,101,196200 There has been extensive research on the differentiation of insulin-secreting beta cells from human pluri- and multipotent stem cells (n = 47 studies), such as hiPSC, 53,106,107,201,202 hESC, 93,195,197199,203206 and MSC. 31,100102,207210 Again, these approaches are based on mimicking the processes of natural pancreas embryology by stepwise reproduction with the addition of growth factors and other molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Scaffold size, mechanical stability, and diffusion distances affect the choice further. Among the in vivo studies included (n = 91) the ISC/scaffold construct was transplanted into subcutaneous locations (n = 31), 27,51,69,9294,112,115,120,133,135,145,147,156,157,171,212225 the peritoneal cavity (n = 19), 18,26,56,63,6568,101,134,135,173,195,226232 an omental pouch (n = 14), 57,59,81,118,119,163,174,225,233238 the renal capsule (n = 18), 54,…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, these hPO integrated into the donor tissue and maintained their phenotypes (Hohwieler, Illing et al 2017). In another study, organoids were engineered via co-culture of three separate cell types (Soltanian, Ghezelayagh et al 2018). Both hPSCderived endothelial cells (EC) and hPSC-derived mesenchymal stem cells (MSC) were established and cocultured with hPSC-derived pancreatic progenitors on growth factor reduced MG to generated hPO.…”
Section: Hepatobiliary and Pancreatic Organoid Transplantationmentioning
confidence: 99%